A New Method of Measuring the Age of Abalone Based on Data Visualization Analysis. Issue 4 (February 2021) - Guo, Runze; Luo, Junmin; Gao, Wuqi
Abstract: This project uses a new way to count the abalone age, which use abalone's physical characteristics to predict by multiple linear regression. After the model is trained, when we catch a new abalone, we can use a computer to replace the labor to a certain extent, saving costs to the enterprise. Results are given in a visualization of the data.